2018
DOI: 10.1515/jpem-2017-0458
|View full text |Cite
|
Sign up to set email alerts
|

Hematuria as an adverse outcome following provocative growth hormone stimulation testing in children

Abstract: In this study of children undergoing GH testing, hematuria was identified in three subjects. This study demonstrates that side effects to agents used for GH testing are self-limited, yet not rare, and should be discussed with patients and families prior to stimulation testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…e prevalence of micro-and macroscopic hematuria in children undergoing GH stimulation testing was measured in a study of 34 subjects undergoing GH stimulation testing using mainly clonidine and arginine [30]. ree subjects (all male; aged 9-12 years) developed hematuria that resolved spontaneously within 7 days of testing, which is congruent with our patient's history.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…e prevalence of micro-and macroscopic hematuria in children undergoing GH stimulation testing was measured in a study of 34 subjects undergoing GH stimulation testing using mainly clonidine and arginine [30]. ree subjects (all male; aged 9-12 years) developed hematuria that resolved spontaneously within 7 days of testing, which is congruent with our patient's history.…”
Section: Discussionsupporting
confidence: 76%
“…e potential pathophysiology of arginine-related hematuria is poorly understood. It has been proposed that transient hypotension experienced by patients who received GH stimulation testing with both clonidine and arginine may cause nephritic changes and subsequent hematuria [30]. Although hematuria can be a marker of glomerular barrier damage, none of the patients in the aforementioned study or our patient had evidence of persistent renal disease.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It has also reported that gross hematuria occurs in a growth hormone stimulation test. 3 In this case, growth hormone was discontinued to check for improvement in the hematuria, but there was no improvement. In this case, there was no causal relationship between the hematuria and growth hormone administration.…”
Section: Discussionmentioning
confidence: 96%